2014
DOI: 10.1002/2013rs005238
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric imaging in Africa

Abstract: [1] Accurate ionospheric specification is necessary for improving human activities such as radar detection, navigation, and Earth observation. This is of particular importance in Africa, where strong plasma density gradients exist due to the equatorial ionization anomaly. In this paper the accuracy of three-dimensional ionospheric images is assessed over a 2 week test period (2-16 December 2012). These images are produced using differential Global Positioning System (GPS) slant total electron content observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
4
18
0
Order By: Relevance
“…The reconstructing techniques used in this work estimate TEC better for the midlatitude than the low latitude. This agrees well with what was previously reported about the performance of IRI (Kumar et al, ) and MIDAS (Chartier et al, ) in low latitude and midlatitude. Generally, the difficulty in reconstructing/modeling the low‐latitude ionosphere has been frequently reported (Adewale et al, ; Kenpankho et al, ; Materassi & Mitchell, ; Panda et al, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The reconstructing techniques used in this work estimate TEC better for the midlatitude than the low latitude. This agrees well with what was previously reported about the performance of IRI (Kumar et al, ) and MIDAS (Chartier et al, ) in low latitude and midlatitude. Generally, the difficulty in reconstructing/modeling the low‐latitude ionosphere has been frequently reported (Adewale et al, ; Kenpankho et al, ; Materassi & Mitchell, ; Panda et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Similar to previous studies (Chartier et al, ; Kumar et al, ; Panda et al, ), storm‐time TEC reconstruction/modeling is more difficult for the low‐latitude than midlatitude ionosphere. The fountain effect and the resulting higher TEC gradients over low‐latitude ionosphere are likely to be the causes of the difficulty in reconstructing/modeling TEC over this region.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A similar approach was used by Chartier et al (2012Chartier et al ( , 2014. Figure 9a and b show the reconstruction obtained with SH and DM.…”
Section: Noise Sensitivitymentioning
confidence: 99%
“…They used a simulated scenario to accurately reconstruct the ionosphere using MART and showed that the reconstruction was highly dependent on the initial guess of the ionosphere. Since then, many other simulations have been conducted to analyze the efficiency of ionospheric tomographic algorithms (Raymund et al 1994, Howe et al 1998, Mitchell and Spencer 2003, Thampi et al 2004, Materassi and Mitchell 2005a, b, Wen et al 2012, Chartier et al 2014, Seemala et al 2014 and for making comparison between ART and MART algorithms for ionospheric studies (Das and Shukla 2011). However, in these simulated studies, the analysis of the efficiency of the algorithms uses climatological models to simulate the ionospheric morphology and/or depends on the real scenario of existing ground-based GNSS receivers used to retrieve the simulated observations of TEC.…”
Section: Introductionmentioning
confidence: 99%